Ferulic acid attenuates high-fat diet-induced hypercholesterolemia by activating classic bile acid synthesis pathway - Luo, Zhixin; Li, Mengqian; Yang, Jiachuan; Li, Jia; Zhang, Yao; Liu, Fang; El-Omar, Emad; Han, Lin; Bian, Ji; Gong, Lan; Wang, Min (Frontiers in Nutrition, 2022)
Ferulic acid (FA), a natural phenolic phytochemical abundantly present in whole grains, displays promising therapeutic effects on hypercholesterolemia while its underlying mechanism not fully elucidated. This study aimed to investigate the cholesterol-lowering effect of FA in high-fat diet (HFD)-fed mice and its potential molecular mechanism. FA supplementation alleviated HFD-induced hypercholesterolemia (-13.2%, p < 0.05), along with increased excretion of bile acids (BAs) in feces (37.0%, p < 0.05). Mechanism studies showed that FA activated the expression of cholesterol 7α hydroxylase (CYP7A1), a rate-limiting enzyme in BA biosynthesis in the liver, which increased the BAs biosynthesis from cholesterol. Surprisingly, increased excretion of BAs in feces is a consequence, not a cause, of CYP7A1 activation. Furthermore, enterohepatic farnesoid X receptor (FXR) signaling is not involved in the activation of hepatic CYP7A1 by FA. In conclusion, FA activates CYP7A1 through non-FXR signaling, which on the one hand effectively prevents hypercholesterolemia, and on the other hand leads to secondary BAs elevation in plasma. The latter may be the key to the anti-obesity and hypoglycemic effects of FA.